Transfer of wafer-scale graphene onto arbitrary substrates: steps towards the reuse and recycling of the catalyst. (10th July 2018) - Seah, Choon-Ming; Vigolo, Brigitte; Chai, Siang-Piao; Mohamed, Abdul Rahman
Abstract: Graphene is a two-dimensional material, a single layer of carbon atoms with a honeycomb lattice, which has increasing demand, especially wafer-scale graphene for applications in electronics industry. However, graphene requires to be supported on different substrates depending on its utilization and the transfer stage must be achieved without damaging the graphene structure. Wet chemical etching is the major route for graphene transfer widely applied right now; the loss of catalyst during the separation process being the main limitation. Mechanical peeling is a simple process but the quality of the separated graphene remains poor. Currently, electrochemical delamination or bubbling method and water assisted delamination are new and most promising methods for both efficient graphene transfer and possible catalyst reuse. This article provides a comprehensive review of the various graphene transfer methods without compromise in catalyst deterioration and it concludes with the future challenges in the domain.